Molecular genetic strategies to identify Obsessive-compulsive disorder (OCD) and schizophrenia candidate genes in a South African sub-population group - Kinnear, C. J. (Craig John) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--University of Stellenbosch, 2007.